A manual for tilapia business management [ - Bhujel, Ram C. (CABI, 2014)
With a practical focus, this book provides a straightforward guide to tilapia business management for farmers and producers. It describes important aspects like practical methods of production, egg incubation, fry rearing, nutrition and facility mainteance, as well as business concerns such as marketing, use of new technologies, accounting and logistics. Also including chapters discussing integrated farming, fish health management and biosecurity, this book is an equally useful resource for fish farm managers, and aquaculture students and researchers.--COVER